Yiyecek-İçecek Sektöründe Sürdürülebilirlik ve Yenilikçi Yaklaşımlar - Taş, Demet; Olum, Emine (Turk Turizm Arastirmalari Dergisi, 2020)
In today’s world the importance of efficient use of natural resources has increased and the use of renewable resources in an effective way has become essential. Factors such as greenhouse gas emissions, destruction of green areas, over-consumption and unconscious use of resources have become a global threat for the near future. In the present review, which focuses on the solution possibilities for such negativities, it is aimed to emphasize the importance of alternative and innovative sustainable practices in the food and beverage industry. For this purpose, national and international literature review was conducted regarding sustainability. With the detailed literature review, innovative internet-supported equipment and smartphone applications that can be used in the food and beverage industry were introduced. Green restaurant activities, the possibility of use of food wastes as biofuels, food banks, digital kitchen appliances and 3D food printers were examined in this context. In the light of the information reviewed in the present study, it is seen that significant gains can be achieved in the long-term period through the reduction of wastes and the conscious use of resources in food and beverage industry.
Keywords: Smart Kitchen Appliances; Dijital Teknolojiler; Yeşil Restorancılık; Internet of Things; Digital Technologies; Nesnelerin İnterneti; Green Restaurant; Akıllı Mutfak Uygulamaları